2020
DOI: 10.1177/1934578x20966191
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 6 Antiallergic Components in Asarum sieboldii Using High-Performance Liquid Chromatography

Abstract: Owing to the side effects of current drugs for treating atopic dermatitis (AD), a chronic disease in the skin, traditional herbal medicine is receiving much attention as an alternative treatment. Asarum sieboldii has traditionally been used to treat colds, fevers, headaches, coughs, neuralgia, chronic bronchitis, asthma, and allergies. In this study, 6 compounds (echinacoside, vanillic acid, kakuol, methyl eugenol, sesamin, and asarinin) in A. sieboldii were analyzed simultaneously using high-performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…There is evidence for the anti-inflammatory [ 134 ], anti-bacterial [ 135 ], anti-fungal [ 132 ], and anti-cancer activity [ 136 ] effects of Asarum sieboldii . Bioactive compounds of Asari radix, including methyl eugenol, sesamin, asarinin echinacoside, vanillic acid, and kakuol, are useful in treating allergies [ 137 , 138 , 139 ]. Xixin (Asari Radix et Rhizoma) can be radix and rhizoma from Asarum sieboldii or Asarum heterotropoides ( Asarum heterotropoides F. Schmidt) [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence for the anti-inflammatory [ 134 ], anti-bacterial [ 135 ], anti-fungal [ 132 ], and anti-cancer activity [ 136 ] effects of Asarum sieboldii . Bioactive compounds of Asari radix, including methyl eugenol, sesamin, asarinin echinacoside, vanillic acid, and kakuol, are useful in treating allergies [ 137 , 138 , 139 ]. Xixin (Asari Radix et Rhizoma) can be radix and rhizoma from Asarum sieboldii or Asarum heterotropoides ( Asarum heterotropoides F. Schmidt) [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Piperonylic acid is an aromatic acid mainly found in black pepper ( Moreira et al, 2021 ). Lots of research results revealed members of the piperonylic acid family had a range of biological activities and were further developed into a commercial drug and widely used in the field of medicine, such as oxolinic acid ( Yamazawa et al, 2021 ; Boycov et al, 2022 ; Quan et al, 2022 ), kakuol ( Jang et al, 2020 ; Matsumoto et al, 2020 ; Sui et al, 2020 ), and miloxacin ( Horie and Nakazawa, 1992 ; Ueno and Aoki, 1996 ; Ueno et al, 2001 ). In addition, piperonylic acid derivatives also showed good activity against bacteria ( Umadevi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 It is of great significance to strictly control the content of ECH in Chinese medicines and pharmaceutical preparations, as well as dynamic monitoring of drug concentrations in the body for its efficacy and the treatment of related diseases. 11 At present, the analysis methods of ECH are mainly based on chromatography, 12,13 which have been universally recognized but require complex sample preparation with poor portability, making on-site detection difficult and high detection cost.…”
mentioning
confidence: 99%